Improving Arts and Humanities Engagement in Ireland's Civic and Community Sphere. Experiences, challenges, and opportunities for researchers based in HEIs - Payne, Elspeth; Patten, Eve; Whelan, Caoimhe (Trinity College Dublin, 2022)
Engaged research is increasingly recognised as integral to addressing national and global societal challenges. Collaboration is also an increasingly important element of university and government policies and a component of both national and European funding schemes. The Arts and Humanities (AH) currently appear to be underrepresented in engaged research initiatives. Researchers may be missing out on (a) the benefits of bringing their work into active dialogue with societies and communities outside the university and (b) access to important funding streams. The CEPRAH portfolio focuses specifically on the experiences, challenges, and opportunities for the AH. It is a resource for individual AH researchers as well as the support staff and management working in HEIs in the Republic of Ireland. The portfolio aims to encourage and enhance future CSO-AH collaboration. The portfolio is primarily based on (i) an in-depth mapping of the existing engaged research landscape, (ii) one-on-one interviews and case studies, and (iii) a networking event. The authors are indebted to all who took the time to talk to us and engage with the CEPRAH project.
An open access portfolio documenting the key findings of the CEPRAH (Community Engagement Praxis for the Arts and Humanities) project led by the Trinity Long Room Hub Arts and Humanities Research Institute, Trinity College Dublin and AONTAS. CEPRAH was funded by an Irish Research Council New Foundations Grant (Strand 1a) and ran from April to December 2021. The CEPRAH project team was Eve Patten (PI), Elspeth Payne, Caoimhe Whelan, Eve Cobain, Joan Cronin, Caitriona Curtis, Leah Dowdall, and Giovanna Lima. We would like all the researchers, engagement practitioners, and CSO practitioners who gave up their time to discuss the experiences, challenges, and opportunities for AH researchers based in HEIs.
Keywords: research impact; societal impact; arts and humanities policy; community; engaged research; methodology; research methodology; CSO; civil society; Creative Arts Practice; Digital Humanities; Identities in Transformation; Making Ireland; Manuscript, Book and Print Cultures; Arts and Humanities Policy; COMMUNITY; CSO; Civil Society; Engaged Research; METHODOLOGY; civil society; research impact; research methodology; societal impact